The Effect of Price Perception and Product Quality on Shoe Purchasing Decisions: A Case Study of PT Yonshoes Products Consumers - Lipandi, Muhammad Ikbal; Pranamulia, Agus; Putra, Mulyana Gustira (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research was conducted with the aim of analyzing the influence of perceived price and quality of shoe products on purchasing decisions at PT Yonshoes. This research uses quantitative methods. The type of data used in this research is primary data. Primary data was obtained based on distributing questionnaires to 100 respondents. Data were analyzed using multiple linear regression analysis techniques.   Keywords: Price perception, Product quality, Buying decision